Improving the extraction of tomato seed oil and the retention of bioactive substances using pulsed electric field technology - Franka Markić; Klara Kraljić; Višnja Stulić; Sanda Pleslić; Tomislava Vukušić Pavičić; Nadica Maltar-Strmečki (Future Foods)
Tomato seeds are by-products of tomato processing and are rich in important bioactive compounds like carotenoids, polyphenols, phytosterols and fatty acids. The aim of this work was to provide insight into bioactive profile and key physicochemical properties of tomato seed oil (TSO) by using a pulsed electric field (PEF) as a pre-extraction process. Influence of PEF treatment parameters on quality of TSO is reflected in concentration of extracted bioactive compounds, antioxidant activity and oxidative stability of TSO. HPLC and GC analysis revealed that lycopene is the major carotenoid with an average concentration of 565.54 mg/mL and linoleic fatty acid is predominant unsaturated fatty acid in TSO. Results obtained in this work indicate that the PEF treatment parameters of 9 min and 0.5 μs provide the best result in extraction and isolation of bioactive components. Due to the high concentration of bioactive compounds, TSO has strong antioxidant activity, which also plays important role in oxidative stability of the oil. The resistance to free radical formation at high temperatures describes the oxidative stability of TSO, which was investigated by EPR spectroscopy and DSC. This study provides important information about the composition and properties of tomato seed oil, which is crucial for future industrial production and consumption.